Pelatihan Kewirausahaan Dalam Peningkatan Ekonomi Masyarakat Desa Tedunan Kecamatan Semidang Alas Maras Kabupaten Seluma - Oktaviana, Nensy; Soleh, Ahmad; Panjaitan, David; Zoniarti, Zoniarti; Sachanovrissa, Silke (Universitas Dehasen Bengkulu, 2025)
Entrepreneurship training activities have a strategic role in encouraging community economic growth, especially in rural areas that have resource potential but have not been optimized to the fullest. This research and community service was carried out in Tedunan Village, Semidang Alas Maras District, Seluma Regency, with the main objective of increasing community knowledge, skills and motivation in the field of entrepreneurship as an effort to drive the local economy. Tedunan Village is one of the villages with abundant natural resources, especially in the agriculture and livestock sectors. However, most of the people still depend on traditional economic patterns with inefficient management. Low access to information, lack of training, and limited capital are the main challenges in developing independent businesses. Therefore, entrepreneurship training is designed as a concrete solution to equip the community with basic skills in managing a business, from planning, production, marketing, to financial management. The methods used in this training include a participatory approach through lectures, group discussions, case studies, and hands-on practice. The training materials included an introduction to the concept of entrepreneurship, identification of local business opportunities, processing agricultural products into high-value products, digital marketing strategies, and small-scale business management. This activity involved various parties, such as the village government, academics, local business actors, and community groups consisting of youth, housewives, and farmers. The results of the training activities showed an increase in the community's understanding of the concept of entrepreneurship and their ability to design and run businesses independently. Some participants even started to initiate small businesses such as local food processing, catfish farming, and handicraft production based on local natural materials. In addition, the training also fostered a collaborative spirit among villagers in forming joint business groups (KUB) as a form of synergy in facing economic challenges.